THE EVOLUTION OF THE CONCEPT OF MARRIAGE IN SOUTH AFRICA: THE INFLUENCE OF THE BILL OF RIGHTS IN 1994 - JA Robinson (Obiter, 2022)
This contribution focuses on the changes that have been brought about by the Constitution of the Republic of South Africa, 1996 with regard to the concept of marriage qua institution. The Act on Recognition of Customary Marriages 120 of 1998 and the decision of the Supreme Court of Appeal in Fourie v Minister of Home Affairs (2005 3 SA 429 (SCA)) are discussed against the background of the Constitution. In the discussion of the Act, the focus falls on the aspects of lobolo and polygyny that have been retained in the Act. It is also indicated that the decision in Fourie may be considered as the logical conclusion of a different approach towards marriage. In both instances, however, there is a deviation from the “one man and one woman” requirement. The conclusion is reached that the application of constitutional norms and prescripts may not result in the structure of marriage being negated as it has developed socio-legally. The suggestion is made, therefore, that in view of the interest of the state in stable relationships to form the cornerstone of society that formal recognition be given to relationships/unions that are characterised by reciprocal obligations of support and responsibility. Such relationships may be called a union, but the institution of marriage should be reserved exclusively for those who, out of religious convictions or cultural reasons, want to enter into a relationship that meets the common law requirement of the concept. Such couples will then be able to conclude not only a legally recognised union, but also a marriage which will be available only to heterosexual couples.